A high isolation dual‐band MIMO antenna array for multiaccess mobile terminals. Issue 3 (March 2015) - Zhai, Huiqing; Zhang, Jian; Li, Tong; Liang, Changhong
ABSTRACT To satisfy more requirements in wireless communication, a compact dual‐band multiple‐input and multiple‐output (MIMO) antenna array is designed for the multiaccess mobile terminals. The proposed MIMO system consists of six elements of two types of planar inverse‐F antennas (PIFAs), including four U‐slit etched PIFAs and two sawtooth U‐slit etched PIFAs. For increasing the isolation between different elements, we mainly adopt three methods in the design, including the disconnected ground plane, the isolation strips, including T‐strips and inverse π‐strips, and also the modified PIFAs. It can be found that all of the elements could operate at 2.55–2.60 GHz around band LTE and 3.51–3.65 GHz for band WiMAX normally while the return loss and isolation are lower than −10 dB and −20 dB, respectively. Besides, the overall dimension of the multiaccess system is 120 × 70 × 10.4 mm3, in which the radiation patterns of the antenna is quasi‐omnidirectional and the envelop correlation coefficient between ports is below 0.5. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:672–677, 2015